ADSORPTION OF CR (III) IONS THROUGH EFFICIENT AND ECO-FRIENDLY ADSORBENTS - A. Shoaib; N. Aslam; N. Aslam (Journal of Animal and Plant Sciences, 2014)
Biosorption technology has evoked tremendous interest to manipulate natural resources as an alternative to expensive and cautionary chemical based procedures opted as purification treatment for industrial effluents. Feasibility of Ficus bengalensis L. (banyan), Ficus religiosa L. (pippal), Helianthus annus L. (sun flower) leaves and Oryza sativa L. (rice) straw were tested for removal of chromium(III) ions from the aqueous solution. Batch trials showed these four adsorbents hold 70-80% adsorption efficiency at dose of 0.5 g, pH 4.5, and at 35 mg L-1 of metal concentration. Fourier Transform Infrared Spectroscopy (FTIR) explored amine (-NH2) and hydroxyl (-OH) as a predominant contributor in binding of Cr(III) on to adsorbents biomass. Both Langmuir and Freundlich sorption isotherms fitted data well at concentrations of 20, 40, 60, 80 and 100 mg L-1 and showed physico-chemical type of adsorption. pH optimization trials at values of 2, 4, 6, 8 and 10, revealed the maximum adsorption efficiency of 80-84% at pH 4 by all adsorbents. The study concluded that the biomass of F. religiosa, F. bengalensis, H. annus and O. sativa could be utilized as naturally abundant, easily available and low cost adsorbents for the removal of Cr(III) ions from dilute aqueous solution (20-100 mg L-1).
Keywords: Biosorption; Cr(III); FTIR; low cost sorbent; metal isotherm; pH